Actual Problems of Teaching a Foreign Language in a Technical University - Nazarov Rustam Irkinovich (Zien Journals, 2022)
The article deals with some problems of foreign language teaching in a technical higher education establishment and some methods of solving the problems are suggested. The author of the article gives tips and advice on learning English. In particular, the ability to learn, to develop logic, selforganization skills, where practice is the main tool. The introduction of multimedia technologies into the teaching process improves the quality of foreign language teaching, makes lessons more effective and interesting
Keywords: learning process; necessary; the goal; resources